Implementation of interprofessional learning in hospital practice - Bente Kvilhaugsvik; Synnøve Hofseth Almås (Wiley, 2023)
Abstract Aim Some universities of applied science struggle with implementing interprofessional learning due to a lack of diversity in professions. The aim of this study was to investigate whether an interprofessional learning model with an informational letter describing interprofessional learning opportunities can provide nursing students in rural areas with sufficient interprofessional learning during internships. Design This qualitative study utilized a hermeneutical approach. Methods A total of 17 individuals participated in focus groups, group interviews and written responses. The data collection: January 2019. Results Four categories were observed: (a) assumptions about interprofessional learning, (b) available interprofessional learning opportunities, (c) hindrances to interprofessional learning and (d) stimulation of interprofessional learning. The conclusion was that interprofessional learning can be implemented to some extent in areas where different professions work, even when only one student is present. A focus on interprofessional collaboration, patient safety and patient flow are valuable interprofessional learning objectives. An informational letter with suggestions for interprofessional learning, such as shadowing, was considered valuable by the participants.